Decreasing Biological Production and Carbon Export Due to the Barrier Layer: A Case Study in the Bay of Bengal - Zhang, Huangchen; Zhou, Linbin; Li, Kaizhi; Ke, Zhixin; Tan, Yehui (Frontiers in Marine Science, 2021)
Freshwater induced barrier layer (BL) is a common physical phenomenon both in the coastal water and open ocean. To examine the effects of BL on the biological production and the associated carbon export, a physical-biogeochemical survey was conducted in the Bay of Bengal. Severe depletions of surface phosphorus and deepening of the nutricline were observed at the BL-affected stations due to vertical mixing prohibition. The lowered surface chlorophyll a and squeezed deep Chl a maximum (DCM) layer resulted in 18% lowered vertically integrated chl a at those stations. The composition of net-sampled zooplankton altered, and the abundance decreased by half at the BL-affected station (29.68 ind. m-3) compared to the unaffected station (55.52 ind. m-3). Such reduction in major zooplankton groups was confirmed by a Video Plankton Recorder (VPR). The VPR observation indicated that lower (by 1/2) abundance of detritus at the BL-affected station, and much lower carbon export flux rates were estimated at the BL-affected station (0.31 mg C m-2 d-1) than the unaffected station (0.77 mg C m-2 d-1). An idealized 1-dimensional nutrient-phytoplankton-detritus model identified that the existence of BL can lead to decreased surface nutrients and phytoplankton concentration, squeezed DCM layer and lowered detritus abundance. Our study indicates that BL layers inhibit biological production and reduce carbon export, and play an important role in the ocean biogeochemical cycles.